'No one is superior to another': tracing intercultural development in a year-long study abroad programme. Issue 5 (3rd September 2022) - Çiftçi, Emrullah Yasin; Karaman, A. Cendel; Daloğlu, Ayşegül
ABSTRACT: Due to its essential role in communication among diverse individuals and human communities, the cultivation of interculturality is among the foremost aims of educational domains. Short-term study abroad can be one way to help students develop interculturality. However, there is a lack of a clear picture regarding the multidimensional impact of short-term study abroad on individuals' intercultural development. There also seems to be no clear consensus on the adequacy of influential intercultural competence models in terms of capturing intercultural development through short-term study abroad. In that regard, we traced an individual's multidimensional intercultural development as part of a year-long study abroad programme. We tested and relied on two major models for the analysis of qualitative data: Milton J. Bennett's developmental model of intercultural sensitivity and Darla K. Deardorff's pyramid model of intercultural competence. We revealed that the participant, following her study abroad period, displayed an increasing alignment with ethnorelativism and cultivated more sensitivity in social justice although there were equivocal socio-political issues in her statements. In addition, her host language skills enabled her to gain richer insights into local practices. Lastly, we problematised the adopted models in terms of linguistic competence, macrocontextual features, and nonlinear and concurrent intercultural developments.